PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS WEB MELALUI LINKTREE PADA MATERI POKOK BANGUN DATAR DI KELAS V SD NEGERI 065853 - Winda Septiana Sianturi; Elvi Mailani; Syahrial; Andri Kristianto (STKIP Subang, 2026)
This study aims to develop web-based Mathematics learning media through linktree on flat shape material in fifth grade elementary school and to determine the level of validity, practicality, and effectiveness. This study uses a 4D development model (Define, Design, Development, Disseminate). The subjects of the study were 20 fifth grade students of SDN 065853 Denai. Data collection techniques were interviews, observations, questionnaires, and tests. Data analysis techniques were carried out using qualitative and quantitative analysis. The results of the study showed that (1) web-based learning media through linktree was declared valid with the validation results of material experts of 82.2% and media experts of 92.7% with the criteria of